The use of epoxidized natural rubber for producing rubber seals of LPG tube valves - Hani Handayani; Mohammad Irfan Fathurrohman; Norma Arisanti Kinasih; Asron Ferdian Falaah (Majalah Kulit, Karet, dan Plastik, 2021)
Rubber seal of Liquifed Petroleum Gas (LPG) tube valves should fulfill Indonesian National Standard (SNI 7655:2010), which has high n-pentane resistance properties. This study aimed to design a rubber seal compound based on epoxidized natural rubber which fulfll SNI 7655:2010 requirements. The formulation of compound were designed by using epoxidized natural rubber with varied levels of epoxidation. Epoxidation reaction was occurred in an epoxidation reactor at 70 ºC for 6 hours with 0.75 mole/mole isoprene unit of hydrogen peroxide and 0.4 mole/mole isoprene unit of formic acid. Mechanical properties, ageing properties, and swelling performance in n-pentane of the modifed natural rubber were tested and the result compared to the minimum requirement of SNI 7655:2010. The result showed that the increasing in epoxidation level made natural rubber becomes more polar so it is more resistant to immersion in n-pentane. Epoxidized natural rubber with levels of 40% and 50% fulfilled specifcations for volume change in accordance with the quality requirements in SNI 7655:2010. The use of natural rubber created good elasticity to all level of epoxidized rubber where these properties are needed for rubber seal of LPG tube valve. However, the formulas of compound were less resistant to aging.